123456789101112131415161718192021222324252627282930313233343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115116117118119120121122123124125126127128129130131132133 |
- from sympy.core.singleton import S
- from sympy.core.symbol import Symbol
- from sympy.functions.elementary.trigonometric import (cos, sin)
- from sympy.physics.vector import ReferenceFrame, Vector, Point, \
- dynamicsymbols
- from sympy.physics.vector.fieldfunctions import divergence, \
- gradient, curl, is_conservative, is_solenoidal, \
- scalar_potential, scalar_potential_difference
- from sympy.testing.pytest import raises
- R = ReferenceFrame('R')
- q = dynamicsymbols('q')
- P = R.orientnew('P', 'Axis', [q, R.z])
- def test_curl():
- assert curl(Vector(0), R) == Vector(0)
- assert curl(R.x, R) == Vector(0)
- assert curl(2*R[1]**2*R.y, R) == Vector(0)
- assert curl(R[0]*R[1]*R.z, R) == R[0]*R.x - R[1]*R.y
- assert curl(R[0]*R[1]*R[2] * (R.x+R.y+R.z), R) == \
- (-R[0]*R[1] + R[0]*R[2])*R.x + (R[0]*R[1] - R[1]*R[2])*R.y + \
- (-R[0]*R[2] + R[1]*R[2])*R.z
- assert curl(2*R[0]**2*R.y, R) == 4*R[0]*R.z
- assert curl(P[0]**2*R.x + P.y, R) == \
- - 2*(R[0]*cos(q) + R[1]*sin(q))*sin(q)*R.z
- assert curl(P[0]*R.y, P) == cos(q)*P.z
- def test_divergence():
- assert divergence(Vector(0), R) is S.Zero
- assert divergence(R.x, R) is S.Zero
- assert divergence(R[0]**2*R.x, R) == 2*R[0]
- assert divergence(R[0]*R[1]*R[2] * (R.x+R.y+R.z), R) == \
- R[0]*R[1] + R[0]*R[2] + R[1]*R[2]
- assert divergence((1/(R[0]*R[1]*R[2])) * (R.x+R.y+R.z), R) == \
- -1/(R[0]*R[1]*R[2]**2) - 1/(R[0]*R[1]**2*R[2]) - \
- 1/(R[0]**2*R[1]*R[2])
- v = P[0]*P.x + P[1]*P.y + P[2]*P.z
- assert divergence(v, P) == 3
- assert divergence(v, R).simplify() == 3
- assert divergence(P[0]*R.x + R[0]*P.x, R) == 2*cos(q)
- def test_gradient():
- a = Symbol('a')
- assert gradient(0, R) == Vector(0)
- assert gradient(R[0], R) == R.x
- assert gradient(R[0]*R[1]*R[2], R) == \
- R[1]*R[2]*R.x + R[0]*R[2]*R.y + R[0]*R[1]*R.z
- assert gradient(2*R[0]**2, R) == 4*R[0]*R.x
- assert gradient(a*sin(R[1])/R[0], R) == \
- - a*sin(R[1])/R[0]**2*R.x + a*cos(R[1])/R[0]*R.y
- assert gradient(P[0]*P[1], R) == \
- ((-R[0]*sin(q) + R[1]*cos(q))*cos(q) - (R[0]*cos(q) + R[1]*sin(q))*sin(q))*R.x + \
- ((-R[0]*sin(q) + R[1]*cos(q))*sin(q) + (R[0]*cos(q) + R[1]*sin(q))*cos(q))*R.y
- assert gradient(P[0]*R[2], P) == P[2]*P.x + P[0]*P.z
- scalar_field = 2*R[0]**2*R[1]*R[2]
- grad_field = gradient(scalar_field, R)
- vector_field = R[1]**2*R.x + 3*R[0]*R.y + 5*R[1]*R[2]*R.z
- curl_field = curl(vector_field, R)
- def test_conservative():
- assert is_conservative(0) is True
- assert is_conservative(R.x) is True
- assert is_conservative(2 * R.x + 3 * R.y + 4 * R.z) is True
- assert is_conservative(R[1]*R[2]*R.x + R[0]*R[2]*R.y + R[0]*R[1]*R.z) is \
- True
- assert is_conservative(R[0] * R.y) is False
- assert is_conservative(grad_field) is True
- assert is_conservative(curl_field) is False
- assert is_conservative(4*R[0]*R[1]*R[2]*R.x + 2*R[0]**2*R[2]*R.y) is \
- False
- assert is_conservative(R[2]*P.x + P[0]*R.z) is True
- def test_solenoidal():
- assert is_solenoidal(0) is True
- assert is_solenoidal(R.x) is True
- assert is_solenoidal(2 * R.x + 3 * R.y + 4 * R.z) is True
- assert is_solenoidal(R[1]*R[2]*R.x + R[0]*R[2]*R.y + R[0]*R[1]*R.z) is \
- True
- assert is_solenoidal(R[1] * R.y) is False
- assert is_solenoidal(grad_field) is False
- assert is_solenoidal(curl_field) is True
- assert is_solenoidal((-2*R[1] + 3)*R.z) is True
- assert is_solenoidal(cos(q)*R.x + sin(q)*R.y + cos(q)*P.z) is True
- assert is_solenoidal(R[2]*P.x + P[0]*R.z) is True
- def test_scalar_potential():
- assert scalar_potential(0, R) == 0
- assert scalar_potential(R.x, R) == R[0]
- assert scalar_potential(R.y, R) == R[1]
- assert scalar_potential(R.z, R) == R[2]
- assert scalar_potential(R[1]*R[2]*R.x + R[0]*R[2]*R.y + \
- R[0]*R[1]*R.z, R) == R[0]*R[1]*R[2]
- assert scalar_potential(grad_field, R) == scalar_field
- assert scalar_potential(R[2]*P.x + P[0]*R.z, R) == \
- R[0]*R[2]*cos(q) + R[1]*R[2]*sin(q)
- assert scalar_potential(R[2]*P.x + P[0]*R.z, P) == P[0]*P[2]
- raises(ValueError, lambda: scalar_potential(R[0] * R.y, R))
- def test_scalar_potential_difference():
- origin = Point('O')
- point1 = origin.locatenew('P1', 1*R.x + 2*R.y + 3*R.z)
- point2 = origin.locatenew('P2', 4*R.x + 5*R.y + 6*R.z)
- genericpointR = origin.locatenew('RP', R[0]*R.x + R[1]*R.y + R[2]*R.z)
- genericpointP = origin.locatenew('PP', P[0]*P.x + P[1]*P.y + P[2]*P.z)
- assert scalar_potential_difference(S.Zero, R, point1, point2, \
- origin) == 0
- assert scalar_potential_difference(scalar_field, R, origin, \
- genericpointR, origin) == \
- scalar_field
- assert scalar_potential_difference(grad_field, R, origin, \
- genericpointR, origin) == \
- scalar_field
- assert scalar_potential_difference(grad_field, R, point1, point2,
- origin) == 948
- assert scalar_potential_difference(R[1]*R[2]*R.x + R[0]*R[2]*R.y + \
- R[0]*R[1]*R.z, R, point1,
- genericpointR, origin) == \
- R[0]*R[1]*R[2] - 6
- potential_diff_P = 2*P[2]*(P[0]*sin(q) + P[1]*cos(q))*\
- (P[0]*cos(q) - P[1]*sin(q))**2
- assert scalar_potential_difference(grad_field, P, origin, \
- genericpointP, \
- origin).simplify() == \
- potential_diff_P
|